STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN PENJUALAN DI SEAFOOD LAGOON RESTAURANT NUSA DUA - I Komang Ira Agustiana; Ni Made Hartini; Isa Dwi Poetranto (Universitas Triatma Mulya, 2022)
The purpose of this research is to analyze the marketing strategy that must be carried out by Seafood Lagoon Restaurant to increase sales. The method used in this research is descriptive qualitative through SWOT analysis techniques consisting of IFAS, EFAS, IFE, EFE and IE. Data collection procedures carried out include interviews, documentation and questionnaires. The sample used in this study was a purposive sampling technique which consisted of 10 respondents consisting of 1) Manager, 2) Sales & Marketing, 3) HRD, 4) Supervisor, 5) Seafood Lagoon Restaurant customers. The results of this study conclude that the scores of IFAS and EFAS are 2.52 and 2.64 in column V, which is the level of growth / stability where the most appropriate strategy applied to increase sales at the Seafood Lagoon Restaurant are market penetration and product development strategies. This research shows that the resulting strategy is very appropriate to solve the problem. This research has implications for the progress of Seafood Lagoon Restaurant in increasing sales